การพัฒนาบทเรียนคอมพิวเตอร์ช่วยสอนบนเว็บเรื่อง การเขียนประโยคสำหรับผู้เริ่มเขียนภาษาอังกฤษระดับปริญญาตรี - ตัณฑ์จิตานนท์, พรหทัย (Community and Social Development Journal, 2011)
บทคัดย่อภาษาไทยไม่สมบูรณ์ The Development of Computer-Assisted Instruction Lessons (CAI) on Web on the Topic of English Sentence Writing for the Beginners at Undergraduate Level The purposes of this research were to construct the CAI Lessons on Web on the topic of English Sentence Writing, to compare the students’ English sentence writing ability before and after using the CAI Lessons on Web and to study their satisfactory towards the CAI Lessons on Web. The target group consisted of 30 undergraduate students (Business English) who enrolled Writing 1 in the first semester of the 2010 academic year at Rajamangala University of Technology Lanna. The research instruments were CAI Lessons on Web, English sentence writing ability tests, and checklists of students’ satisfactory level towards the CAI Lessons on Web. All instruments were developed and tried out by the researcher. The effectiveness was assessed in terms of comparing the standard criteria set. The data obtained were analyzed by mean of percentage, mean and standard deviation. The findings of the study were the CAI Lessons on Web on the topic of English Sentence Writing was very effective (E1/E2 = 83.27/ 89.33), the students’ mean scores of the English sentence writing ability post test (after using the CAI Lessons on Web) were higher than those of the pre-test 30.34 percent, and the students were satisfied with and had high positive attitudes towards the CAI Lessons on Web ( = 4.17).